Effect of ciprofol on the incidence of hypotension during induction of general anesthesia in elderly patients undergoing total hip arthroplasty: single-center retrospective study - Zhu, Jiaxi; Chen, Yun; Cao, Ying; Gan, Yicai; Zhang, Xingan; Xu, Bo (Frontiers in Medicine, 2026)
ObjectivePost-induction hypotension (PIH) represents a frequent perioperative complication among elderly patients, and its prevention is critical for reducing organ damage and postoperative adverse outcomes. This study aims to evaluate the impact of ciprofol on the incidence of PIH when used for general anesthesia induction in elderly patients.MethodsA retrospective review was carried out on the clinical records of elderly patients who underwent elective total hip replacement surgery at our hospital between August 2024 and July 2025. Patients were stratified into the ciprofol group and the propofol group based on the anesthetic sedative agents administered. The primary outcome indicator was PIH, characterized as a mean arterial pressure (MAP) ≤65 mmHg or a reduction greater than 30% relative to baseline values within 20 min post-induction. Subgroup analyses included considerations of preoperative hypertension, the Clinical Frailty Scale (CFS), the age-adjusted Charlson Comorbidity Index (aCCI), and patient age.ResultsBaseline clinical features were comparable across groups. The incidence of PIH was markedly lower in the ciprofol group than in the propofol group (36.4% vs. 65.5%; absolute risk reduction = 29.1, 95% confidence interval: 11.2–47.0%, p = 0.002). Subgroup analyses demonstrated that the advantages of ciprofol remained consistent across all pre-specified subgroups, with prominent differences noted in patients aged under 90 years, those with an aCCI of ≤4, a CFS score of ≤4, and baseline blood pressure (BP) of <140/90 mmHg.ConclusionCiprofol reduces PIH risk, improves haemodynamic stability, and decreases vasoactive agent use and injection pain compared with propofol in elderly patients, independent of baseline characteristics, indicating suitability for anesthetic management in this population.